Comparative study between face-to-face job satisfaction and teleworking in a mixed system in Portugal - Morgado, Tiago Miguel Veloso da Silva Paulo (2022)
Teleworking these days is something that is seen as very normal. With the appearance of Covid-19 it became a mandatory measure for most companies. Fortunately, with the emergence and constant evolution of information and communication technologies, teleworking has become possible in this most difficult time that the world has gone through. Even before Covid-19 appeared, teleworking was already very important in companies' strategy and in their innovation, as it contributed to greater competitiveness in companies. At this stage, the pandemic is under more control, with a large percentage of the population already vaccinated. That said, this study aims to compare job satisfaction between workers who work face-to-face and those who work in a mixed regime, that is, both works face-to-face and telework. In this comparative study, an online survey will be carried out, with the objective of obtaining qualitative and quantitative data that demonstrate which way of working brings more satisfaction to workers. The study involves a sample of 178 employees from various professions. After a careful analysis of the results, we concluded that, based on the responses to the survey, the way of working that brings more satisfaction to workers is when the worker is in a mixed system. In comparison with the mixed system and face-to-face work, all the questions revealed that the mixed system causes greater satisfaction, such as professional and personal life.